The Blood Brain Barrier and Inflammation - Lyck, Ruth; Enzmann, Gaby (Springer International Publishing : Imprint: Springer, 2017)
Within the central nervous system (CNS) the constantly changing blood stream is separated from the CNS parenchyma by the blood brain barrier (BBB) restricting passage to selected immune cells. Under pathological conditions, however, viruses, bacteria, parasites and autoaggressive immune cells can penetrate the barrier and contribute to CNS inflammation. The BBB actively contributes to neuroinflammation by presentation of chemokines, expression of cell adhesion molecules and alteration of barrier properties. As such, understanding the role of the BBB under healthy and pathological conditions is essential for the development of new drugs to efficiently combat inflammatory diseases of the CNS. This book presents a comprehensive collection of reviews that focus on the role of the BBB. Experts in the field share their insight on structural, topological and functional properties of the BBB. They elaborate on pathophysiological changes of the inflamed BBB such as permeability, transporter proteins and alterations in microRNAs and cytokine profile. Additional chapters on multiple sclerosis and bacterial meningitis provide in depth information on significant neuroinflammatory diseases. The selection is complemented by a review on the current understanding of the BBB as signaling hub in tumor pathogenesis in the brain.
Keywords: Medicine.; Immunology.; Neurosciences.; Infectious diseases.; Cytokines.; Growth factors.; Cell membranes.; elektronické knihy; electronic books